Immunosuppression with Antitumour Necrosis Factor Therapy Leading to Strongyloides Hyperinfection Syndrome. (30th May 2018) - Khaliq, Muhammad Farhan; Ihle, Rayan E.; Perry, James
Abstract : Strongyloides stercoralis is an endemic parasitic infection that can remain asymptomatic for years, but it can cause death in immunosuppressed individuals. Here, we present a case of Strongyloides hyperinfection in a 75-year-old male secondary to sepsis and chronic immunosuppression due to TNF- α inhibitors. Despite aggressive treatment including broad-spectrum antibiotics and antihelminths, his respiratory failure worsened and he died after palliative extubation. S. stercoralis infection remains a diagnostic challenge. Presentation with Strongyloides is often nonspecific, and eosinophilia is absent in hyperinfection. Diagnosis can be delayed, especially in low-prevalence areas where suspicion is low. Strongyloides should be considered in the differential diagnosis in the presence of risk factors including immunosuppressive therapy, and a travel history should be carefully obtained. Patients with recurrent enterobacterial sepsis or respiratory failure with diffuse infiltrates in the setting of eosinophilia should undergo testing for Strongyloides . A multidisciplinary approach can result in earlier diagnosis and favorable outcomes.